Konseling Individu dengan Pendekatan Behavioral bagi Pelaku Kekerasan Seksual di UPTD PKS Insan Berguna - Fitriyanti, Risma; Nasution, Sri Ilham; Mawarni, Anisa (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2024)
This research aims to describe the implementation stages of individual counseling using a behavioral approach for perpetrators of sexual violence at the UPTD PKS Insan Berguna, Lampung Province Social Service. Children involved in sexual violence need a more advanced approach, such as through guidance and counseling that focuses on recovery. Individual counseling is effective because it involves direct interaction between the counselor and the client, allowing the counselor to pay more in-depth attention to the problems faced by the client. The method used in this research is a field research method. Data collection techniques in this research used observation, interviews and documentation. The results obtained in this research show that individual counseling with a behavioral approach has an effect on changing clients' good behavior. The main focus of this research is to describe the behavior patterns of these children, as well as the changes that occur in the rehabilitation process carried out at that place. Researchers also try to explain how a counseling process based on a behavioral approach can help these children identify and change their behavior patterns to be more positive. And clients are starting to realize the impact of their bad habits and are actively working to change them. After attending this counseling, the three clients realized their mistakes and will now try to change for the better. Individual counseling with a behavioral approach shows effectiveness in dealing with behavioral problems, but also emphasizes that self-awareness is an important first step in efforts to improve lifestyle. Furthermore, the behavioral changes achieved by clients during the counseling process provide hope that this kind of intervention can contribute to a sustainable improvement in their quality of life.